20 years after To Err Is Human: a bibliometric analysis of ‘the IOM report’s’ impact on research on patient safety - St. Pierre, Michael; Grawe, Petra; Bergstrom, Johan; Neuhaus, Christopher (Safety science, 2022)
Modern safety science owes much of its current theories and practical approaches to the critical analysis of socio-technological disasters in the nuclear, chemical, maritime, and aviation industries at the end of the 1970 s and in the 1980 s. The medical field by contrast, was not challenged by a single high profile event, but by the release of a single report by the Institute of Medicine in 1999: To Err is Human - Building a Safer Health System. The report expanded the level of conversation and concern about patient injuries in health care and led to an unprecedented provision of research grants in patient safety research, essentially launching the academic base for that work. Twenty years later, it is a good time to analyze how this seminal work was received in the academic literature, which authors and institutions had the greatest research activity, which national and international collaborations ensued, and how the ideas presented in To Err Is Human might have affected the academic discourse in the two decades to follow. To meet this aim, a bibliometric analysis was performed on all publications from 2000 to 2019 where the authors referenced To Err Is Human as part of their scientific argument. 20.494 documents were retrieved. The majority of patient safety related research was carried out by researchers from North America, with little international collaboration. Over the years, the thematic scope of the research diversified from the IOM report’s initial focus in many directions. Contrary to what might be expected from the IOM report’s central objectives, research on a systems approach to patient safety and on incident reporting were underrepresented. From a safety science perspective, the report narrowed the diversity of the patient safety discourse rather than enlarging it by favoring the theoretical framework proposed by James Reason over other, equally valid ones.
Available online 26 November 2021
Gesehen am 17.06.2022